Sustainable Supply Chain Management in the Apparel Industry: A Critical Analysis and Awareness of Female Labor Empowerment - Zahin, Zinia (2018)
There is extensive research in the area of sustainability and its importance for long-term growth and prosperity, however not much has been contributed towards the social dimension of sustainability, especially when concerning the subject of female labor and the issue of empowerment in the context of fashion. This paper studies whether the fashion Multinational Companies (MNCs) lead to empowerment or exploitation of the women workforce at factory level of global supply chains. Offering an empirically constructed response to the notion of empowerment and strategies from a critical realist point of view, this research addressed the actual level of empowerment experienced by the women. I examine the exploited condition of women workforce in developing countries, and how an image for sustainable global supply chain structured around a fabricated construction of empowerment limits what is seen as desirable, admissible and possible. A multimodal critical discourse analysis is adopted to study the empowerment image constructed through various contents (websites, reports, videos and statements) released by the renowned organization H&M. This paper reveals the underlying strategies of a care-based morality, fabrication of the truth, mechanism of power, and oppression of women within the sustainable imaginary, therefore showing how “empowerment” is manipulated to create dependencies for the unprivileged women. Decontextualization helps address how aware of the exploited situation the fashion MNCs actually are, and the supply chain risks that originate from the lack of awareness. Finally, this dissertation presents a framework for sustainable empowerment that considers the cooperation of all parties involved to construct an ideal win-win situation.